Corporate responsibility and the recession: learning from responsible businesses - Barnor, Abiola (Cranfield University School of Management, 2009)
Research done by several prestigious organisations shows that businesses’ desire to be corporately responsible has not fared too badly in this recession, despite widespread job cuts, shrinking budgets and reprioritisation among corporate, third and governmental sectors. This is the first global recession in which the concept of corporate responsibility (CR) is part of standard business language, and 2009 has seen growth in global understanding of the effect of bad governance on corporate systems and economies, and acceptance and action on climate change and resource scarcity. The increase in the delivery of truly sustainable business and the lack of written evidence of CR behaviour in past recessions suggests that the effect of the current recession on CR is worth investigating. Equally as important are the potential changes likely to occur following this recession. These changes may be either external and market driven or internal and strategy driven. The post-recession period will be characterised by lessons from recession times informing new ways of doing business and strengthening current business models that have been systematically delivering value over the last few years (e.g. social and environmental enterprises). We need to start thinking about what this means for them in the long term. We need to know where emphasis and focus has shifted and why, and how businesses view these shifts in relation to their longer term planning. We need to share best practice among each other, to inform our actions for the future and to encourage a competitive approach to increasing standards of being a sustainable business. This occasional paper is based on a research project in the summer of 2009 by the author as part of her MSc studies, combined with the experience and knowledge of the Doughty Centre and the kind insight and assistance of experts in the discipline of CR, as reviewers. The purpose is to contribute to the existing knowledge on CR behaviour as well as generate new and topical advice for CR practitioners. The research findings presented in this paper are generated from academic research using three separate data collection methods: interviews in summer 2009 with nine responsible companies based in the UK defined as ‘responsible businesses’ by inclusion in the BITC CR Index; desk research from a literature search; and a survey conducted on-line among CR practitioners in the UK from businesses generally, across a range of 24 organisations. The paper is divided into two key sections: research findings from the specific pool of resources used in this research and our subsequent observations; and recommendations to readers using the observations from the research as well as the knowledge and experience of the authors and reviewers who contributed to the paper.